Seed-free electrodeposition of ZnO bi-pods on electrophoretically-reduced graphene oxide for optoelectronic applications. Issue 2 (March 2015) - Pruna, A.; Reyes-Tolosa, M.D.; Pullini, D.; Hernandez-Fenollosa, M.A.; Busquets-Mataix, D.
Abstract: Large areas of reduced graphene oxide (rGO) films were obtained by electrophoretic deposition onto insulating glass substrate. ZnO nanostructures were directly grown on the rGO films by single-step electrodeposition method. The properties of ZnO nanostructures were evaluated as a function of deposition mode onto rGO electrodes with different stoichiometry. Atomic force microscopy (AFM), X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetrical analysis (TGA), transmission measurements, Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) were employed to characterize the obtained materials. Bi-pod morphology was observed for ZnO electrodeposited on rGO films by pulsed current elelctrodeposition. The obtained ZnO/rGO hybrid structures show high potential for highly transparent optoelectronic nanodevices.